TANTANGAN INTEROPERABILITAS REKAM MEDIS : STUDI KASUS DI RUMAH SAKIT SINGAPARNA MEDIKA CITRAUTAMA - Wahyuni, Ida; Heryawan, Lukman; Sanjaya, Guardian Yoki; Prabowo, Tony (Jurnal Manajemen Kesehatan Indonesia, 2024)
Background: Health transformation in Indonesia is aimed at achieving one health data. Health data interoperability is the key to comprehensive health services. Integration can be done if a sistem is interoperable. This case study was conducted at a local government hospital in West Java Province. Concerning the vision of national interoperability, it is important to assess interoperability readiness.Objective: To explore the interoperability challenges of medical records in RSUD SMC Tasikmalaya.Method: A qualitative research design through in-depth interviews with 11 participants to explore the interoperability of medical records based on the framework of interoperability maturity aspects.Results: The interoperability of medical records at RSUD SMC is in the preparation phase. Device standardization as a sistem compatibility requirement has been implemented. Currently, hospitals are faced with technical interoperability challenges, both compliance with medical record data variables, sistem quality challenges, and medical record information quality, as well as data security in hospitals. For this reason, maturity support is needed in aspects of information technology leadership and governance to strengthen digital investment and vendor cooperation. The functionality of human resources in the implementation of information sistems through the support of human resource capacity building for front and back-end developers, medical record experts, and data engineers is in line with the strengthening of technology infrastructure. Conclusion: To improving  quality of the RME interoperability, management of the three aspects of leadership and governance, HR, and technology in hospitals is urgently needed for further strategies for organizational interoperability.